Internalized stigma and its association with hope, self-esteem, self-efficacy, and treatment adherence among outpatients with severe mental illness: A cross-sectional survey - Samira Hamidi; Hossein Ebrahimi; Maryam Vahidi; Hossein Namdar Areshtanab (Wolters Kluwer Medknow Publications, 2023)
Background: This study investigated the association between internalized stigma and hope, self-esteem, self-efficacy, and treatment adherence and explored the most influential and predictive factor of internalized stigma among patients with severe mental disorders. Materials and Methods: This correlational descriptive study was conducted on 257 outpatients diagnosed with severe mental illness according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) diagnostic criteria. The participants were seeking treatment at outpatient and affiliated clinics of Razi Hospital, Iran, from October 2018 to May 2019. We used a convenient sampling design. Internalized Stigma of Mental Illness scale, Dispositional Hope Scale, Rosenberg's Self-Esteem Scale, General Self-Efficacy Scale, and Drug Attitude Inventory were used to gather data. The data were analyzed using inferential statistics (Pearson correlation, coefficient logistic, and regression analyses) at a 0.05 significance level. Results: The mean (standard deviation) score of internalized stigma was 1.57 (0.49), and 58% of the participants reported moderate to high internalized stigma. A negative significant relationship was found between internalized stigma and hope (r = −0.55, p < 0.05), self-esteem (r = −0.66, p < 0.05), and self-efficacy (r = −0.64, p < 0.05). Treatment adherence was not found to be significantly associated with the internalized stigma. In the final regression model, self-esteem and self-efficacy significantly predicted internalized stigma. Conclusions: Given the crucial role of self-esteem and self-efficacy in predicting internalized stigma, nurses should devote special attention to these factors and use strategies to improve individuals' self-esteem and self-efficacy.